THE QUALITY OF EDUCATION IN RURAL AREAS FROM THE PERSPECTIVE OF PRIMARY AND SECONDARY SCHOOL TEACHERS - Mihaela PREDA; Elena TOMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The rural education development is a strategic objective in Romania, especially due to the present challenges like: the drop in the number of students, poverty, lack of infrastructure, etc. The pressure to the sector was even higher during pandemic period when the rural educational infrastructure wasn’t prepared for the infrastructural necessities. The present paper aimed to analyse the quality of education in rural areas from Arges county by a survey among 107 teachers from 7 middle schools and 1 high school, situated in five rural villages. The results revealed the needs of the teachers from rural areas to assure a good education, the needs of students to learn, the measures needed to be implemented regarding curricula, teaching methods and learning techniques.